Intravitreal triamcinolone acetonide combined with subthreshold grid laser treatment for macular oedema in branch retinal vein occlusion: a pilot study. Issue 8 (12th June 2008) - Parodi, M B; Iacono, P; Ravalico, G
Abstract : Background: To compare the effectiveness of subthreshold grid laser treatment (SGLT) with infrared micropulse diode laser alone or in combination with intravitreal triamcinolone injection (SGLT-IVTJ) for the treatment of macular oedema (MO) secondary to branch retinal vein occlusion (BRVO). Methods: Pilot randomised clinical trial including 24 patients (24 eyes) who were randomised either to the SGLT (13 eyes) or to SGLT-IVTJ (11 eyes). Complete ophthalmic examinations, including Early Treatment of Diabetic Retinopathy Study visual acuity, OCT and fluorescein angiography, were performed at the moment of the study entry and at 3-month intervals, with a planned follow-up of 12 months. Main outcome measures were the decrease in mean foveal thickness (MFT) on OCT, and the proportion of eyes that gained at least 10 letters (approximately two or more lines of visual acuity gain) at the 12-month examination. Secondary outcomes were the decrease in mean total macular volume on OCT, and the timing of MO resolution. Results: The change in MFT from the initial values was statistically significant for the SGLT-IVTJ from the 3-month examination and for the SGLP from the 6-month examination (p<0.001). At the 12-month evaluation, 10 patients of the SGLT-IVTJ group (91%) and eight of the SGLT group (62%) gained at least 10 letters (two lines) in visual acuity. The mean number of lines gained was 3.4 and 1.3 in the SGLT-IVTJ and in the SGLT group, respectively. Conclusions: The combined SGLT-IVT treatment of MO secondary to BRVO allows a significant visual acuity improvement, when compared with simple grid laser treatment.